2007
DOI: 10.1016/j.trstmh.2006.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological investigation of an outbreak of acute diarrhoeal disease using geographic information systems

Abstract: An outbreak of acute diarrhoeal disease in a village in southern India was investigated through personal interviews of all households. Maps were drawn using geographic information system (GIS) tools of the water supply system, sewage channels and areas with observed faecal contamination of soil within and around the village. Geographic coordinates for each house in the village were extracted from a central database from the healthcare service provider for the village. Geographical clustering of cases was looke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 11 publications
0
39
0
Order By: Relevance
“…31 Open air defecation, a common practice among villagers, may lead to contamination of the water supply system and result in outbreaks of diarrheal disease. 32,33 Open air defecation more common in our study than other rural area of Salem district. 31 Open air defecation close to human dwellings contributed to the conversion of large areas of land in and around the village into "defecation or faecal fields.…”
Section: Discussionmentioning
confidence: 50%
“…31 Open air defecation, a common practice among villagers, may lead to contamination of the water supply system and result in outbreaks of diarrheal disease. 32,33 Open air defecation more common in our study than other rural area of Salem district. 31 Open air defecation close to human dwellings contributed to the conversion of large areas of land in and around the village into "defecation or faecal fields.…”
Section: Discussionmentioning
confidence: 50%
“…[3][4][5][6] Even when population-based methods of water purification, such as chlorination of tanks, are successful, practices in the home, such as dipping tumblers or cups into wide-mouthed containers to obtain water, can cause recontamination. 7 Studies have shown that in the absence of recontamination, counts of thermotolerant coliforms will decrease significantly over hours to days in stored water samples.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to prevent future outbreaks included improvement of infrastructure [45,46], change of policy [29,32,47] and generation of risk maps [48]. Luquero and colleagues, for instance, used results of their analysis to recommend specific regions in which to focus preparedness activities to avoid future cholera outbreaks in Guinea-Bissau [49].…”
Section: Executing Prevention Measuresmentioning
confidence: 99%
“…Several studies also highlighted the usefulness of maps in reports or Reports by continent presentations to communicate results to health officials [29,47], policymakers [49,50] and the public [38]. Sarkar and colleagues, for example, presented dot maps of cases of acute diarrhoeal disease in a village in southern India to the local community and health authorities [46]. Their maps visualised the proximity of cases to a contaminated water supply, and the presentation resulted in release of funds to improve sanitation in the area.…”
Section: Communicating Findingsmentioning
confidence: 99%